YRNAs: biosynthesis, structure, functions and involvment in cancer development - Adele Campo; Federica Aliquò; Tania Velletri; Salvatore Campo (Discover Oncology)
Abstract Y RNAs are a class of highly conserved small non-coding RNAs. Emerging evidences reported that Y RNAs and their Y RNA-derived small RNAs (YsRNAs) represent bioactive molecules and not simply structural RNAs involved in scaffolding and assembling. They can interact and regulate both localization and functions of several RNA-binding proteins implicated in a wide range of cellular processes such as DNA replication, RNA quality control and cellular stress responses. More evidences suggest functional involvement of Y RNAs in several type of disease such as cancer, immune related pathologies, neurological disorders and cardiovascular diseases. Nevertheless, there are many questions that still need to be answered for their functional and mechanistic understanding in a physiological and in a pathological context. In this review we will describe the current state of knowledge about YRNAs, their structure, biogenesis, functions and interaction with known proteins, as well their role in disease. The picture arising indicates their potential function as biomarkers for disease diagnosis, as well as therapeutical targets for building up tailored approaches in personalized medicine.